PENGARUH PENGGUNAAN MEDIA BUSY BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI PAUD TERPADU FILOSOFIA KUBU BABUSSALAM ROKAN HILIR - Nilmayani '; Devi Risma; Zulkifli N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the aim of this research is to know the effect of busy book media towards early reading ability in children aged 5-6 years In kindegarten Terpadu Filosofia Kubu Babussalam Rokan Hilir from April to Mei 2017. This is pretest and posttest control group design an experimental research with 26 children as samples. Type of instrument used in this study is the observation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the Media’s is influence on ability to read busy book starters in children aged 5-6 years In kindegarten Terpadu Filosofia Kubu Babussalam Rokan Hilir. Retrieved tcount at 7,005 with sig 0000, because sig <0.05 then we can conclude that there are influence on the ability to read is significant between class with Busy Book Media and without Busy Book Media. Hypothesis testing can be seen at tcount= 7,005> t table = 2,064 it has been suggested that there is a significant influence in results between the control class and experiment class. The Busy Book Media had a significant effect towards children’s age 5-6 years old ability to read, at 70%. This is known from the different results ability to read on control class and expriment class with given the Busy Book Media treatment.Keywords: Reading Starters, Busy Book